Pengaruh Proses Rekrutmen (Porek) dan Seleksi terhadap Kinerja Karyawan PT. BANK MAYA PADA INTERNASIONAL, Tbk - Nurul Aisyah; Angelia Giovanni (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2018)
Human resources is an asset that plays an important role in a company, because humans who manage and run activities that exist within the organization. One of the most influential aspects in achieving the objectives of a company is recruitment and selection of work, because recruitment and selection is a condition that moves people to a particular destination. Recruitment and selection of work can benefit employee and company performance. method is the authors take descriptive quantitative by using the sample technique saturated, the number of respondents as much as 50 respondents using SPSS version 22. In the results of research authors can know, that the relationship of recruitment and selection of a very strong performance that is equal to 0.887 (89%) the influence of recruitment and selection on performance. The amount of coefficient of determination 0,786 or equal to 78,6%, while the rest is 21,4% (100% -78,6%) explained by other causal factors and significant level of 0.000 then H1 accepted, regression equation significant, so that regression equation that can be formed is: Y = 7,722 + 0,802X, therefore the existing level of motivation must be maintained and should be further improved especially in the employee's own performance.